Genotype and clinical course in 2 Chinese Han siblings with Wilson disease presenting with isolated disabling premature osteoarthritis: A case report. Issue 47 (November 2017) - Ye, Siyuan; Dai, Tingjun; Leng, Bingquan; Tang, Lei; Jin, Liang; Cao, Lili
Abstract: Rationale: Premature osteoarthritis (POA) is a rare condition in Wilson disease (WD). Particularly, when POA is the only complaint of a WD patient for a long time, there would be misdiagnosis or missed diagnosis and then treatment delay. Patient concerns and diagnosis: Two Chinese Han siblings were diagnosed as WD by corneal K-F rings, laboratory test, and mutation analysis. They presented with isolated POA during the first 2 decades or more of their disease course, and were of missed diagnosis during that long time. The older affected sib became disabled due to his severe osteoarthritis when he was as young as 38 years old. Two compound heterozygous pathogenic variants c.2790_2792del and c.2621C>T were revealed in the ATP7B gene through targeted next-generation sequencing (NGS). Lessons: Adolescent-onset POA could be the only complaint of WD individual for at least 2 decades. Long delay in the treatment of WD's POA could lead to disability in early adulthood. Detailed physical examination, special biochemical test, and genotyping through targeted NGS should greatly reduce diagnosis delay in atypical WD patients with isolated POA phenotype. Abstract : Supplemental Digital Content is available in the text